The Effect Of Customer Relationship Management On Consumer Behavior: A Case Of Retail Industry In Malaysia - Walid Abdullah Al-Suraihi; Al-Hussain Abdullah Al-Suraihi; Ishaq Ibrahim; Ali Al-Tahitah; Mohammed Abdulrab (Lincoln University College, 2024)
Non-Indexed Publication